Workshop Penulisan Artikel Ilmiah dan Metode Penelitian - Lady Faerrosa; Raden Bagus Faizal Irany Sidharta; Zahrah; Isra Dewi Kuntary Ibrahim; Baiq Dinna Widiyasti (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
The hardest part of doing research for some people is writing a research background and choosing the right research methods. The purpose of holding community service in the form of workshops with the theme of Scientific Article Writing and Research Methods is to provide training and guidelines for writing scientific papers and choosing the right research methods. The target of this community service is young lecturers / researchers of the Management Study Program, students of Semester V and Semester VII of S1 Management, Bumigora University. This workshop activity is considered important because the author realizes that new students and lecturers or researchers still need guidance to understand more deeply the steps that need to be done in each research phase. Community service in the form of workshops like this is expected to be a forum for lecturers and universities to provide guidance and knowledge to the target community, especially new students and lecturers. In addition, considering the importance of workshops with this theme, it is also hoped that this service activity can be a reference and inspiration for other institutions to hold similar activities.